Organometallic Half-Sandwich Iridium Anticancer Complexes - Liu, Zhe; Habtemariam, Abraha; Pizarro, Ana M.; Fletcher, Sally A.; Kisova, Anna; Vrana, Oldrich; Salassa, Luca; Bruijnincx, Pieter C. A.; Clarkson, Guy J.; Brabec, Viktor; Sadler, Peter J. (Journal of medicinal chemistry, 2011)
The low-spin 5d(6) Ir-III organometallic half-sandwich complexes [(eta(5)-Cp-x)Ir(XY)Cl](0/+), Cp-x = Cp*, tetramethyl(phenyl, cyclopentadienyl (Cp-xph), or tetramethyl(biphenyl)-cyclopertadienyl (Cp-xbiph), XY = 1,10-phenanthroline (4-6), 2,2'-bipyridine (7-9), ethylenediamine (10 and 11), or picolinate (12-14), hydrolyze rapidly. Complexes with N,N-chelating ligands readily form adducts with 9-ethylguanine but not 9-ethyladenine; picolinate complexes bind to both purines. Cytotoxic potency toward A2780 human ovarian cancer cells increases with phenyl substitution on Cp*: Cp-xbiph > Cp-xph > Cp*; Cp-xbiph complexes 6 and 9 have submicromolar activity. Guanine residues are preferential binding sites for 4-6 on plasmid DNA. Hydrophobicity (log P), cell and nucleus accumulation of Ir correlate with cytotoxicity, 6 > 5 > 4, they:distribute similarly within cells. The ability to displace DNA intercalator ethidium bromide from DNA correlates with cytotoxicity and viscosity of Ir DNA adducts. The hydrophobicity and intercalative ability of Cp-xph and Cp-xbiph male a major contribution to the anticancer potency of their Ir-III complexes.